Pilot Study of the Efficacy of Constraint-Induced Movement Therapy for Infants and Toddlers with Cerebral Palsy. (1st February 2014) - Lowes, Linda Pax; Mayhan, Marianne; Orr, Teresa; Batterson, Nancy; Tonneman, Jill Alyce; Meyer, Angela; Alfano, Lindsay; Wang, Wei; Whalen, Cara N; Nelin, Mary Ann; Lo, Warren David; Case-Smith, Jane
ABSTRACT The evidence for Constraint-Induced Movement Therapy (CIMT) effectiveness for infants and toddlers with unilateral cerebral palsy is minimal. We performed a pilot study of CIMT using one-month usual care, one-month intervention, and one-month maintenance (return to usual care) phases on five infants (7- to 18-month old). For the CIMT phase, the infants received 2 hr of occupational therapy and 1 hr of parent-implemented home program for five days/week. The infants were casted for the first 23 days, and bimanual therapy was provided for the last three days. Fine motor skills for the more affected arm and gross motor skills improved significantly during the CIMT; these gains were maintained at one-month follow-up. Individual infant data show mixed effects. This pilot study provides initial evidence that CIMT is feasible for infants with unilateral cerebral palsy, and presents preliminary data for CIMT on fine and gross motor performance.